Highly Efficient Clay Based Degumming Aid for Phosphorous Removal from Crude Palm Oil - Bajpai, Indu; Pal, Pawan; Bhasin, Sanjeev (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2023)
The removal of phosphorous from crude oil is a complex and necessary step to enhance the oxidative stability and shelf life of edible oil. In this aspect, the current work proposed clay based degumming aid for the removal of phosphorous from the crude palm oil during the bleaching process. The state of art qualitative and quantitative techniques was adopted for the study of physical and chemical properties of different raw materials and oil. A profound study on the stability of the degumming aid is based on the assessment of phosphorous removal efficiency with time (up to 6 months) and bleachability. The results of current work revealed that clay based degumming aid is highly effective in removing phosphorous up to 96%. Additionally, the bleaching performance of clay-based aid is also palpable (around 45%), which influences the deodorization process of the crude palm oil positively. The clay based degumming aid eliminate separate degumming process with acids, which directly impact the oil processing time and cost. Overall, proposed clay based degumming aid is highly efficient, stable for long time and cost effective as well, for the removal of undesired phosphorous from the crude palm oil during the bleaching process.